Leonurine: a comprehensive review of pharmacokinetics, pharmacodynamics, and toxicology - Liu, Siyu; Sun, Chen; Tang, Hailin; Peng, Cheng; Peng, Fu (Frontiers in Pharmacology, 2024)
Leonurine is an alkaloid unique to the Leonurus genus, which has many biological activities, such as uterine contraction, anti-inflammation, anti-oxidation, regulation of cell apoptosis, anti-tumor, angiogenesis, anti-platelet aggregation, and inhibition of vasoconstriction. This paper summarizes the extraction ways, synthetic pathways, biosynthetic mechanisms, pharmacokinetics properties, pharmacological effects in various diseases, toxicology, and clinical trials of leonurine. To facilitate a successful transition into clinical application, intensified efforts are required in several key areas: structural modifications of leonurine to optimize its properties, comprehensive pharmacokinetic assessments to understand its behavior within the body, thorough mechanism studies to elucidate how it works at the molecular level, rigorous safety evaluations and toxicological investigations to ensure patient well-being, and meticulously conducted clinical trials to validate its efficacy and safety profile.